2014
DOI: 10.1021/ja508127q
|View full text |Cite
|
Sign up to set email alerts
|

Complete Biosynthetic Pathway of Anditomin: Nature’s Sophisticated Synthetic Route to a Complex Fungal Meroterpenoid

Abstract: Anditomin and its precursors, andilesins, are fungal meroterpenoids isolated from Aspergillus variecolor and have unique, highly oxygenated chemical structures with a complex bridged-ring system. Previous isotope-feeding studies revealed their origins as 3,5-dimethylorsellinic acid and farnesyl pyrophosphate and suggested the possible involvement of a Diels-Alder reaction to afford the congested bicyclo[2.2.2]octane core structure of andilesins. Here we report the first identification of the biosynthetic gene … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
182
0
3

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 172 publications
(191 citation statements)
references
References 53 publications
6
182
0
3
Order By: Relevance
“…The biosynthesis of intriguing meroterpenoids metabolized by Aspergillus and Penicillium has been investigated for decades, and recently the molecular bases (biosynthetic genes/enzymes) for five 3,5-dimethylorsellinic acid (DMOA) and farnesyl pyrophosphate derived meroterpenoids, andrastin A, austinol, terretonin, anditomin, and berkeleydione, have been reported [20][21][22][23][24][25][26][27][28][29] and thoroughly reviewed. [30] Notably, the completely elucidated pathways for austinol [21,22,27] and berkeleydione, [29] for which the known compounds preaustinoid A1 (7) and preaustinoid A3 (10) acquired here are biosynthetic intermediates, enabled us to propose detailed mechanisms for the biosynthesis of the five related new meroterpenoids 1-5 (Scheme 1).…”
Section: Hr-esi-ms Analysis Of 1-methoxy-hydropreaustinoid A1 (3) Yiementioning
confidence: 99%
“…The biosynthesis of intriguing meroterpenoids metabolized by Aspergillus and Penicillium has been investigated for decades, and recently the molecular bases (biosynthetic genes/enzymes) for five 3,5-dimethylorsellinic acid (DMOA) and farnesyl pyrophosphate derived meroterpenoids, andrastin A, austinol, terretonin, anditomin, and berkeleydione, have been reported [20][21][22][23][24][25][26][27][28][29] and thoroughly reviewed. [30] Notably, the completely elucidated pathways for austinol [21,22,27] and berkeleydione, [29] for which the known compounds preaustinoid A1 (7) and preaustinoid A3 (10) acquired here are biosynthetic intermediates, enabled us to propose detailed mechanisms for the biosynthesis of the five related new meroterpenoids 1-5 (Scheme 1).…”
Section: Hr-esi-ms Analysis Of 1-methoxy-hydropreaustinoid A1 (3) Yiementioning
confidence: 99%
“…Representative examples are found in the total biosynthesis of tenellin, 11 aphidicolin, 12 paxilline, 13 aspyridone, 14 aflatrem, 15 and anditomin (11 + 1 genes). 16 For skeletal construction of 1 in A. oryzae, bet1 and bet3 genes were subcloned into fungal expression vectors, pUARA2 (argB marker) and pUSA2 (sC marker), 15 to construct pUARA2-bet1 and pUSA2-bet3, which were then introduced into A. oryzae NSAR1 to construct both a bet1 single transformant and a bet1/3 double transformant ( The 1 H-NMR spectrum of the product completely agreed with that of 4, 9 allowing us to determine the structure of the observed metabolite as 5. These results showed that the collaborative action of Bet1 and Bet3 plays a key role in the skeletal construction of 5 in betaenone biosynthesis.…”
mentioning
confidence: 99%
“…The mononuclear nonheme iron oxygenases are likewise an important family of oxidative catalysts, as illustrated by AndA and AndF, which have recently been characterized for their roles in the generation of complexity, including the bicyclo [2,2,2] core of the anditomin meroterpenoids in fungi (Fig. 1b) 4 . Also important for particular natural product classes are flavin coenzyme-linked oxygenases 5 and even oxygen-linked halogenases, as seen in the generation of the trichloromethyl group in barbamide formation (Fig.…”
Section: Between Genes and Moleculesmentioning
confidence: 99%